Inovasi Peningkatan Kualitas Pelayanan Publik dalam Penerapan Sistem Check-In dan Boarding Pass pada PT KAI DAOP I Jakarta (Studi Kasus Layanan Check In dan Boarding Pass di Stasiun Senen Jakarta) - Raymundus I Wayan Ray (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2020)
Abstract The purpose of this study is to analyze and examine the innovations in improving the quality of public services in the application of the check-in and boarding pass systems at Pasar Senen Jakarta Station. As for the background of the implementation of the check-in and boarding pass system is to remember the need for people to use train services every year is increasing, while the fact is that many people take advantage of this situation with the practice of brokering fake tickets. Besides that, PT. KAI wants to increase its work productivity by implementing innovations to improve the quality of public services that prioritize modern technology. The research method used in this study is a qualitative method using descriptive research. The focus of this study uses indicators according to Zeithamal Parasuraman Berry's theory (in Hariyanto (2013: 17) there are five dimensions of public service quality that can be used to measure the quality of public services, namely: a) Direct evidence (tangibles). B) Reliability (reliability) .c ) Responsiveness. d) Guarantee and. e) Empathy. Data collection techniques used were observation, interviews and documentation. Based on the results of this study indicate that innovation in improving public services in the application of the Check-In and Boarding Pass system is quite good, when compared to self-ticket printing (CTM) it can be seen from interviews with service officers and service users that an increase in the quality of public services every year. Besides that, in terms of the efficiency of the prospective train passengers will feel facilitated by the service that is fast and precise and not convoluted, so that prospective train passengers feel quite satisfied with the results of services provided by PT. KAI DAOP I, Pasar Senen Station Jakarta.